Conservation of the avian biodiversity in paddy (Oryza sativa) crop agroecosystem - BORAD, C K; MUKHERJEE, AESHITA; PARASHARYA, B M (The Indian Journal of Agricultural Sciences, 2013)
The quantity of shattered rice (Oryza sativa L.) grains was estimated in 12 freshly harvested rice fields during 1997in Kheda district, Gujarat. Average quantity of shattered grains was 106.26 kg/ha ranging from 50.06 kg/ha to 198.19 kg/ha. Total 98 % grains was depleted within 4 week period atter harvesting; 60 % within first week and remaining 38 % within next 3 weeks. Total 67 bird species consumed crop residues, which became exposed after harvesting, of which the ruff Phylomacus pugnax, eastern skylark Alauda gulgula, and yellow wagtail Motacilla flava were predominant. The grains and fauna exposed due to harvesting activity over 2 months period had very high value for conservation of the avian biodiversity.Â